A parsimonious fundamental model for wholesale electricity markets: Analysis of the plunge in German futures prices - Thomas Kallabis; Christian Pape; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2015)
The German market has seen a plunge in wholesale electricity prices from 2007 until 2014, when base futures prices dropped by more than 40 percent. In this paper we determine the fundamental components of electricity futures prices and quantify their impact on the price drop as well as on operation margins. Our methodology is based on a parsimonious model in which the supply stack is approximated by piecewise linear functions. A fundamental futures price estimate can then be given by averaging up the hourly equilibrium prices over the futures contract's delivery period. It turns out that the parsimonious model is able to replicate electricity futures prices and discover non-linear dependencies in futures price formation. We quantify which of the factors fuel prices, emission prices, renewable feed-in, conventional generation capacities, and demand developments contributed most to the observed price slide.
Keywords: 330; Futures Prices; Bid Stack; Fundamental Factors; German Electricity Market; Price Modeling; Efficient Markets; Market Expectations; Piecewise Linear Function; Investment Decision